Photodynamic Therapy Using HMME for Port-Wine Stains: Clinical Effectiveness and Sonographic Appearance. - Khalaf, Ahmad Taha; Sun, Yonghong; Wang, Fang; Sheng, Minmin; Li, Yan; Liu, Xiaoming (BioMed Research International, 2020)
This study aims at exploring the clinical efficacy and sonographic changes of photodynamic therapy (PDT) using Hematoporphyrin Monomethyl Ether (HMME) for the treatment of port-wine stains (PWS). Forty-five patients with PWS were recruited between March 2017 and June 2018 from the Department of Dermatology of The Third Affiliated Hospital of Soochow University. Five cases were of the pink type, thirty-nine cases were of the purple-red type, and one case was of the thickened type. All patients received three treatment sessions of PDT. After covering normal skin outside the treated area, patients received an intravenous injection of 5 mg/kg HMME within 20 minutes. The affected areas were exposed to a 532 nm LED light and were kept vertically at a distance of 10 cm. The irradiation energy density was set between 80 and 110 J/cm2 in 15-minute sessions. Intermittent power density adjustment was performed at a rate of 5 mW/cm2, and the treatment was withheld when the endpoint reaction appeared. Three follow-ups were performed before and after treatment, respectively, and the efficacy, thickness, and density of skin before and after treatment were evaluated with high-frequency ultrasound. The overall efficacy rate was 97.78% in forty-five cases after treatment for three sessions. Efficacy was related to age (P = 0.029) and lesion severity (P < 0.001). There were significant differences in the efficacy between the groups of <18 years old, 18-29 years old, and >29 years old (P = 0.029). A marked decrease in the numbers of distorted enlarged blood vessels per unit of the lesion was observed under high-frequency ultrasound. There were significant differences in skin thickness and skin density before and after treatment (F = 14.528 , 5.428, P < 0.001). The swelling was reported to varying degrees in the treated areas in 23 patients with cheek lesion and in 6 frontal lesions. Hyperpigmentation after inflammation was observed in four patients that faded spontaneously after two months. In conclusion, photodynamic therapy for the treatment of PWS using HMME is effective and safe with few adverse reactions. Moreover, monitoring the changes in skin thickness and density of lesion tissue using high-frequency ultrasound can objectively evaluate the clinical efficacy of HMME photodynamic therapy and provide the basis for the formulation of individualized photodynamic therapy.